Abnormal Trichuris trichiura eggs detected during an epidemiological survey - Ferrer-Rodríguez, Iván; Kosek, Wieslaw J. (Puerto Rico Health Sciences Journal, 2007)
Abnormal eggs of Trichuris trichiura were found in the stools of one of the patients during a study on the prevalence of intestinal parasitoses among an institutionalized population. The abnormalities observed included great variation in shape, size, and color. Similar atypical whipworm eggs have been reported in patients after treatment with mebendazole, thiabendazole, tetracloroethylene, and dithiazanine. Apparently some anthelminthics have an effect on the reproductive system of female T. trichiura, resulting in production of abnormal eggs, which could lead to misdiagnosis of the infection, since they can be mistaken as eggs of other parasites or artifacts.